Et la forêt brûla sous nos pieds - Arthur Guérin-Turcq; Caroline Paulus; Antonin Renard (Projets de Paysage)
The fire in July 2022 in the La Teste-de-Buch forest gave rise to a unique pyropathic landscape, reflecting the socio-ecosystem that formed at the foot of the Pilat Dune to the south of the Arcachon Basin on the Atlantic coast of south-west France. Our article looks at the conflicting representations caused by the emergence of the landscape following the disaster. It is based on a study of the upheavals in the landscape caused by the fire in the La Teste-de-Buch forest, a forest which is exceptional in terms of its legal and political status. Fires of this size are unprecedented and spectacular and at the same time they are recurrent symptoms of climate change. Following the example of Joelle Zask (2019), who defines a megafire as ‘a total event’, we show that the fire created a new landscape reshaping the relationship between the local community and this forest common. We also analyse the conflicts that now shape the decisions to be taken regarding risk prevention, the dynamics of the regeneration of the forest, and the reconstruction of the forestry huts. The fire thus highlights the symbolic values of the forest landscape, which is associated with nature and life.